Investigation Performance and Mechanisms of Inverted Polymer Solar Cells by Pentacene Doped P3HT : PCBM - Hsin-Ying Lee; Hung-Lin Huang (International Journal of Photoenergy)
The inverted polymer solar cells (PSCs) with pentacene-doped P3HT : PCBM absorption layers were fabricated. It was demonstrated that the pentacene doping modulated the electron mobility and the hole mobility in the resulting absorption layer. Furthermore, by varying the doping content, the optimal carrier mobility balance could be obtained. In addition, the pentacene doping led to an improvement in the crystallinity of the resulting films and made an enhancement in the light absorption, which was partly responsible for the performance improvement of the solar cells. Using the space-charge-limited current (SCLC) method, it was determined that the balanced carrier mobility (μh/μe=1.000) was nearly achieved when a pentacene doping ratio of 0.065 by weight was doped into the P3HT : PCBM : pentacene absorption layer. Compared with the inverted PSCs without the pentacene doping, the short circuit current density and the power conversion efficiency of the inverted PSCs with the pentacene doping ratio of 0.065 were increased from 9.73 mA/cm2 to 11.26 mA/cm2 and from 3.39% to 4.31%, respectively.